Elderly Onset of Weakness in Facioscapulohumeral Muscular Dystrophy. (18th September 2012) - Fee, Dominic B.
Abstract : A 77-year-old male is presented. He had onset of proximal weakness 10 years earlier. His course was slowly progressive. Despite having phenotypic features of facioscapulohumeral muscular dystrophy (FSH), genetic testing for this was delayed because of his age of onset, lack of family history, and benign appearing muscle biopsy. This case is one of the oldest onset of weakness in genetically confirmed FSH and highlights the recognized expansion in phenotype that has occurred since the advent of genetic testing.